2018
DOI: 10.1016/j.compedu.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a digital formative assessment tool on spelling achievement: Results of a randomized experiment

Abstract: In this study, a randomized experimental design was used to examine the effects of a digital formative assessment tool on spelling achievement of third grade students (eight-to nine-yearsolds). The sample consisted of 30 experimental schools (n = 619) and 39 control schools (n = 986). Experimental schools used a digital formative assessment tool, whereas control schools used their regular spelling instruction and materials. Data included standardized achievement pre-posttest data, the number of total assignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
(20 reference statements)
0
16
0
2
Order By: Relevance
“…We identified only seven studies (Borman, Benson, and Overman 2009;Deault, Savage, and Abrami 2009;Faber and Visscher 2018;Mitchell and Fox 2001;Rouse and Krueger 2004;Wijekumar, Meyer, and Lei 2012;Wijekumar et al 2014) within the developed world exclusively examining reading and spelling programs. Of these, two evaluated Fast ForWord, a program initially designed for students with particular learning disabilities (Rouse and Krueger 2004;Borman, Benson, and Overman 2009), but that has been, in some cases, marketed and used to cope with broader reading challenges.…”
Section: Experimental Evidencementioning
confidence: 99%
“…We identified only seven studies (Borman, Benson, and Overman 2009;Deault, Savage, and Abrami 2009;Faber and Visscher 2018;Mitchell and Fox 2001;Rouse and Krueger 2004;Wijekumar, Meyer, and Lei 2012;Wijekumar et al 2014) within the developed world exclusively examining reading and spelling programs. Of these, two evaluated Fast ForWord, a program initially designed for students with particular learning disabilities (Rouse and Krueger 2004;Borman, Benson, and Overman 2009), but that has been, in some cases, marketed and used to cope with broader reading challenges.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Furthermore, researchers have developed relevant computer‐assisted formative assessment tools, such as the digital formative assessment tool snappet, the intelligent tutoring system writing‐Pal (Roscoe & Mcnamara, 2013), and the Digital Information Skills Measurement (Timmers, Walraven, & Veldkamp, 2015). These assessment tools have been applied to specific subject areas, such as spelling, for example, Faber and Visscher (2018), writing, for example, Lachner, Burkhart, and Nückles (2017), and mathematics, for example, Faber et al (2017). It has been shown that most of these tools are basically separated from manual assessment, gradually turn to semi‐automatic or automated assessment (Febriani & Abdullah, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Nawas [9] stated that students are more confident, they feel happy when they are doing exercise responisbility about their peers' writing. Moreover, Faber and Visscher [12] indcated that peer assessment supports students to be independet and improves proficinecy in high knowledge area. They acknowledge the definite weakness of this kind of assessment.…”
Section: Introductionmentioning
confidence: 99%